Analisis Kepuasan Pengguna terhadap Sistem Repositori di Perpustakaan Universitas Negeri Malang - Syavira Zeta Firdaulia Dasmasela; Citra Kartika Sari; Rani Auliawati Rachman; Rahma Dwi Astuti; Farah Difa Agustina; Joko Aiko Ponco Wicaksono (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
This study evaluates the success of the institutional repository system at Universitas Negeri Malang (UM) using the DeLone & McLean Model (2003). A descriptive quantitative approach with a survey design was used to measure user satisfaction. Using a purposive sampling technique, data were gathered from 103 active student users and analyzed via SPSS version 26 software. Results show that overall user satisfaction falls into the moderate-to-high category. However, multidimensional testing revealed critical barriers in system quality; the close access policy indicator (A6) scored low at 3.019, and ease of access for various groups (E1) scored 3.165. Conversely, the repository content guarantee (C1) achieved the highest score at 3.990, and time-saving (E2) scored 3.903. Contextual data confirms that full-text restrictions trigger user complaints and lower the university's Webometrics ranking. Consequently, this study recommends a gradual transition toward open access, faster document upload verification, and improved synchronization between physical and digital document availability to maximize the repository's net benefits.